Undertaking insurance preservation from the hadith of the Prophet (O young man, Be mindful of Allah and Allah will protect you) - et. al., Adel Harb Basher AL- asasmeh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Summary of the study in Arabic: The aim of preservation and legislative insurance is to ensure a comfortable life for the Muslim, away from troubles and worries, and to fulfill his obligations of Allah. So Allah believes for him his future in this world and the hereafter, and Allah asks of him for things on which his comfort depends, so that he preserves his relief, tongue and eyesight, so Allah preserves him from the dangers of predestination, and will enter Paradise eternal happiness, to the extent that whoever recites the last two verses of Surat Al-Baqarah. He memorized it throughout his day, and whoever recites the Ayat al-Kursi( verse of chair); Satan did not approach him.